Influence of Polymorphonuclear Leukocytes on the Metabolism of Arachidonate in Human Platelets - Oudinet, Jean-Paul; Sraer, Josée; Bens, Marcelle; Ardaillou, Raymond (Thrombosis and Haemostasis, 1988)
The effect of the association of purified polymorphonuclear leukocytes (PMNL) with platelets on arachidonic acid (AA) metabolism was studied in the presence of various concentrations of this fatty acid. Both thromboxane B2 (TXB2) and 12-hydroxyeicosatetraenoic acid (12-HETE) were measured. In the presence of tracer doses of AA, addition of increasing amounts of PMNL to platelets inhibited in a concentration-dependent manner their 12-HETE and TXB2 production. This inhibition was not due to diversion of AA metabolism towards other pathways since, apart a negligible amount of 12,20-diHETE, no other product could be detected. Inhibition of piatelet-TXB2 synthesis by PMNL persisted at increasing concentrations of AA below 16 μM. Above this concentration, TXB2 production by platelets incubated alone diminished progressively. Addition of PMNL blunted in part this inhibitory effect and even resulted, above 16 μM AA, in an increased production of TXB2. In contrast with what was observed for TXB2 formation, the inhibition of 12-HETE synthesis persisted when PMNL and platelets were coincubated in the presence of high doses of AA (163 μM). At this concentration, 15-HETE generation became apparent for each cell type incubated separately and was markedly enhanced in the coincubation studies. The present investigation demonstrates that the presence of PMNL modifies the metabolism of arachidonate by human platelets. Moreover, this cell-cell interaction markedly depends on the concentration of substrate. PMNL in excess may attenuate synthesis by platelets of their toxic products.
Keywords: Polymorphonuclear leukocytes; Platelets; Thromboxane; 12-hydroxyeicosatetraenoic acid; Arachidonic acid